Perancangan Alat Ukur Intensitas Cahaya menggunakan Sensor BH1750 Berbasis Mikrokontroler ATMega328P - Tominikus Benyamin Bano; I Gusti Agung Widagda; Ni Luh Putu Trisnawati; I Made Satriya Wibawa; I Ketut Putra; I Nengah Sandi (Universitas Hamzanwadi, 2024)
The design of a light intensity measuring instrument using the BH1750 sensor based on the ATMega328P microcontroller has been successfully created. The results of light intensity data are measured by using the BH1750 sensor which receives a data signal in the form of light intensity. In order to get results that are in accordance with the reference tool, the design of a light intensity measuring instrument by using the BH1750 sensor based on the ATmega328P microcontroller is carried out in the Electronics and Instrumentation Laboratory and Computing Laboratory, Physics Study Program, FMIPA, Udayana University, Jimbaran, Bali. Then the results of the design of tool and reference tool processed into graphical form and proven by employing a linear regression equation. The measurement results of light intensity are displayed on a 16x2 LCD. The test results of the design tool against the reference tool shown that the level of accuracy of the design tool is relatively high.